Model Pembelajaran Nahwu dengan Media Chart di Pesantren Salafiyah - Marwaji, Deden; Akmansyah, Muhammad; Amiruddin, Amiruddin; Koderi, Koderi; Erlina, Erlina (Journal of Arabic Language Studies and Teaching, 2025)
This study presents a literature review on the development of a Nahwu learning model using chart media in Salafiyah Islamic boarding schools. The main problem is the difficulty students face in understanding i’rab and Arabic grammar rules through traditional methods such as lectures and memorization. This study aims to analyze the effectiveness of chart media as a visual tool that simplifies complex grammatical concepts, evaluate the challenges and opportunities in its implementation, and formulate theoretical and practical contributions to improve Nahwu learning. A systematic review approach was used to review national and international journal articles published over the last 5–15 years. The findings of this study indicate that chart media promotes better conceptual understanding, increases student engagement, and provides pedagogical innovations relevant to the pesantren context. This study concludes that the chart-based model has a significant impact.